A method for scaling impressions of a scene. Issue 5 (13th May 2020) - Liu, Tzuhao; Hutchings, John; Luo, Ming Ronnier
Abstract: This article describes the results of an experiment to evaluate people's impressions of a live landscape scene, the famous West Lake in Hangzhou, China. We invited seventy students from different academic backgrounds to participate in this project. The goals of this study were to find a method for the evaluation of the perception of a live scene, to reveal differences for subjects from different backgrounds, and to provide a method for teaching students. In the experiment, students sat together and looked at the lake from one similar location. The whole scene was divided into five parts, and the students were asked to give their judgment of those five different subjects. The results were analyzed to find the main components describing the scene. The novel features in the work involved the assessment of the scene using a large number of people, to have observers from various backgrounds, and to provide a new teaching method for colour science and colour design.